IMPROVED ACTIVE SOUND REDUCTION SYSTEM - Lizunov , Sergey; Filobok, Evgenij (Ukrainian Information Security Research Journal, 2022)
Usually, to eliminate the leakage of information through the acoustic channel, either sound insulation or generators of correlated acoustic noise are used. In the first case (passive method) requires a significant amount of time to carry out sound insulation work. In the second case (active method), the presence of noise generators creates discomfort during negotiations. The radiation itself is an unmasking sign, which makes it easier for attackers to determine the time and place of negotiations. The disadvantages of both of the above methods can be partially eliminated by using active noise reduction systems (Active Noise Control, Active Noise Cancellation, ANC, Active Noise Reduction, ANR). Active noise reduction systems are based on the process of wave interference. These systems are most effective at handling noise from 100 Hz to 1 kHz. Despite the fact that the method itself allows you to effectively suppress ambient sounds, real devices do not always cope with this task, especially with acoustic vibrations with a frequency of more than a thousand Hertz. The fact is that it takes some time for microcontrollers to register the sound and calculate the opposite wave. Because of this, the sound they emit is no longer completely opposite to the incoming sound, but lags behind it in phase. This disadvantage can be reduced if the signal to be suppressed is fed to the input of such a device via an electric or electromagnetic channel. Due to the fact that the electrical signal travels faster than sound, the device starts to process the signal even before it arrives in the form of an acoustic wave. Thanks to this microcontroller has time to pick up the "opposite" sound that is in phase with the original, with less late. The noise reduction of such systems works for sounds with a frequency of up to 4 kHz. Thus, at the boundaries of the controlled area, it is possible to reduce the level of acoustic waves from the sources of regime information to a safe value. Such systems can also be successfully used in secure rooms where the circulation of acoustic (speech) information is prohibited by regulatory documents or instructions. Further improvement of such a system is possible if we take into account the following dependencies (characteristics) of the room between the location of the sound that is suppressed (speaker) and the points of the acoustic information leakage channels at the boundaries of the controlled area: temporary (time of propagation of an acoustic wave), frequency (amplitude-frequency response and phase-frequency response), reverberation (reflection of sound waves from obstacles). These characteristics can be taken in advance and entered into electronic control units that generate suppressing signals. In this case, each block is ready in advance for converting the signal received from the microphone in order to develop the most effective suppression signal. Thus, in principle, it is possible in general to refuse the use of additional microphones around each channel of speech information leakage. Further improvement of the active sound suppression system is aimed at increasing the efficiency, concealment of the fact and place of negotiations, and reducing the power consumption of the system.